rdlc 2020
DOI: 10.7764/rdlc.19.1.68-79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curing conditions during the first 24 hours after casting on the properties of mortar mixtures

Abstract: As it is well known, the curing method directly affects many properties of cementitious composites. In previous studies, the effect of different curing conditions on the properties of the cementitious systems has been generally investigated in the period after first 24 hours after casting. However, there are not many studies in the literature related to the effects of curing conditions on the specimens kept in mold during 24 hours after casting. In this study, strength development, ultrasonic pulse velocity (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In addition, strength gain was about 69 %, 34 %, 44 % for samples produced using fine, medium, and coarse hemp shiv aggregates with the increase of H:W ratio from 2.5 to 3.0, respectively. These might be as a result of decreasing water content of mixtures with the increase of H:W ratio, consistent with the prior literature (Mardani-Aghabaglou et al, 2020;Singh et al, 2015).…”
Section: Compressive Strengthsupporting
confidence: 92%
“…In addition, strength gain was about 69 %, 34 %, 44 % for samples produced using fine, medium, and coarse hemp shiv aggregates with the increase of H:W ratio from 2.5 to 3.0, respectively. These might be as a result of decreasing water content of mixtures with the increase of H:W ratio, consistent with the prior literature (Mardani-Aghabaglou et al, 2020;Singh et al, 2015).…”
Section: Compressive Strengthsupporting
confidence: 92%
“…It was emphasized that this concern was caused by the main factors such as not using formwork 83 and lack of curing process in 3DPC samples. It was reported that these parameters accelerate shrinkage and consequently increase the risk of cracking 84–86 . As it is known, plastic shrinkage is observed in cases where the evaporation rate is higher than the bleeding rate and causes shallow cracks on the surface 87,88 .…”
Section: Dimensional Stability Of 3dpc Mixturesmentioning
confidence: 99%
“…It was reported that these parameters accelerate shrinkage and consequently increase the risk of cracking. [84][85][86] As it is known, plastic shrinkage is observed in cases where the evaporation rate is higher than the bleeding rate and causes shallow cracks on the surface. 87,88 Compared to 3DPC mixtures, it is expected that the evaporation of pore water will be delayed and the severity of plastic shrinkage will be less as a result of the use of formwork and curing in conventional concretes.…”
Section: Shrinkagementioning
confidence: 99%
“…Curing temperature histories affects the strength development of high strength concrete as well as normal concrete [3]. Therefore, the curing condition in the initial stage, especially fresh concrete temperature affects the rate of compressive strength development [4][5]. Several methods can be used to reduce the initial temperature of fresh concrete, such as: using chilled water, ice, chilled air, liquid nitrogen, and aggregate cooling.…”
Section: Introductionmentioning
confidence: 99%